2011
DOI: 10.1039/c0dt01369b
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of phosphinites with oxide surfaces: a new method for anchoring organic and organometallic complexes

Abstract: When a pincer-ligated iridium complex with a phosphinite substituent in the para-position of the aromatic backbone is immobilized on γ-alumina, it becomes a highly effective supported catalyst for the transfer-dehydrogenation of alkanes. The nature of the interaction between the organometallic complex and the support was investigated using solid-state (31)P MAS NMR spectroscopy, solution-state (1)H and (31)P{(1)H} NMR spectroscopy, IR and GC/MS analysis of extracted reaction products. The phosphinite substitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 20 publications
2
34
0
1
Order By: Relevance
“…Previous studies also showed significant up-field chemical shifts for the pincer ligands and their complexes upon immobilization on to solid supports. [28] However, CPMAS 13 C resonances of the immobilized PONOP ligand and their complexes showed good agreement with the resonances found in solution (δ 163.1, pyridine ; δ 35.5, tert-butyl carbons). [47][48][49] Solid-state CPMAS 13 assigned to the CH and CH 2 -groups of poly(allylamine) and the propyl anchors bound to the starting BP-1.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Previous studies also showed significant up-field chemical shifts for the pincer ligands and their complexes upon immobilization on to solid supports. [28] However, CPMAS 13 C resonances of the immobilized PONOP ligand and their complexes showed good agreement with the resonances found in solution (δ 163.1, pyridine ; δ 35.5, tert-butyl carbons). [47][48][49] Solid-state CPMAS 13 assigned to the CH and CH 2 -groups of poly(allylamine) and the propyl anchors bound to the starting BP-1.…”
Section: Resultssupporting
confidence: 54%
“…and binding of para-functionalized POCOP iridium pincers to a coordinately-unsaturated surface Al site in Al 2 O 3 . [28] The dihydride pincer complex [IrH 2 (POCOP)] was also anchored on a mesoporous silica (SBA-15) by reaction of hydride with surface silanol groups and utilized as a heterogeneous catalyst for alkene hydrogenation reactions. [29] Pd(II)-SCS pincer complexes were covalently immobilized on porous silica, poly(norborene) and cross-linked Merrifield resin supports by C.W.…”
Section: Scheme 1: General Formula For Pincer Ligand-complexes and Comentioning
confidence: 99%
“…Thea ctive sites of these key petrochemical processes are proposed to be isolated metal sites.S ections 3.2 and 3.3 will describe heterogeneous dehydrogenation catalysts (both oxidative and non-oxidative) based on supported isolated metal sites generated by SOMC; [42,43,45,46] their activity will be compared to the related systems prepared by using classical methods.T he alternative approach based on supported homogeneous catalysts [84][85][86] has recently been reviewed and will not be discussed. [87] …”
Section: Industrial Context and Backgroundmentioning
confidence: 99%
“…In den Abschnitten 3.2 und 3.3 werden Heterogenkatalysatoren für die nichtoxidative und oxidative Dehydrierung mit isolierten, durch SOMC erzeugten Metallzentren beschrieben, deren Aktivität verwandten, durch klassische Verfahren hergestellten Systemen gegenübergestellt wird. Der alternative Ansatz mit trägerfixierten Homogenkatalysatoren wurde erst kürzlich in Übersicht beschrieben und wird hier nicht weiter diskutiert …”
Section: Dehydrierung Von Alkanenunclassified